Deep insight into eye-tracking in glottodidactics Agnieszka Andrychowicz-Trojanowska, Podręczniki glottodydaktyczne: Struktura — funkcja — potencjał w świetle badań okulograficznych, Warszawa, Wydawnictwo Naukowe IKSI, pp. 563 - Żelazowska-Sobczyk, Magda (Przegląd Krytyczny, 2024)
Eye-tracking technology has become more prevalent in science and research. It has already been used in social sciences, management, marketing (e.g. Stolecka-Makowska & Wolny, 2014), computer/video gaming, as well as linguistics (Grucza et al., 2014), including translation studies, and glottodidactics, i.e. foreign language teaching and learning (see Grucza, 2020).